2002
DOI: 10.1016/s0341-8162(01)00180-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate stability as an indicator of soil susceptibility to runoff and erosion; validation at several levels

Abstract: The evaluation of soil susceptibility to runoff and water erosion in the field is often expensive or time-consuming. Several authors have reported that susceptibility is linked to aggregate stability, whose determination is far easier. However, this susceptibility has generally been deduced from rainfall simulation experiments on sieved soil samples, whose behaviour is not always representative of field-scale phenomena. Our aim was to extend the validity of relationships between soil aggregation and erosion th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
278
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(299 citation statements)
references
References 26 publications
11
278
2
8
Order By: Relevance
“…The runoff and water erosion on sandy soil were significantly reduced by the compost application. In earlier studies was reported that the aggregate stability is negatively correlated with erosion and runoff (Barthes and Roose, 2002;Kroulík et al, 2010). Thus, the application of sewage sludge compost improves the structure of sandy soil.…”
Section: Resultsmentioning
confidence: 97%
“…The runoff and water erosion on sandy soil were significantly reduced by the compost application. In earlier studies was reported that the aggregate stability is negatively correlated with erosion and runoff (Barthes and Roose, 2002;Kroulík et al, 2010). Thus, the application of sewage sludge compost improves the structure of sandy soil.…”
Section: Resultsmentioning
confidence: 97%
“…Soil structure was considered as one of the more important indicators of soil erosion (Barthès and Roose, 2002;Amezketa et al, 1996). It is closely related to the movement of water in the soil through physical properties such as water storage capacity, bulk density, and porosity (Truman and Bradford, 1990;Deuchras et al, 1999;Barthès and Roose, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is closely related to the movement of water in the soil through physical properties such as water storage capacity, bulk density, and porosity (Truman and Bradford, 1990;Deuchras et al, 1999;Barthès and Roose, 2002). In addition, organic carbon increases the formation of soil aggregates (Casermeiro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Besides a substitution of energy and nutrients, and a stimulation of the internal processes in soil governed by the microbial community, the application of biowaste compost in agricultural soils may positively affect soil organic-matter (SOM) content and soil-aggregate stability (Balesdent et al, 2000;Wahlen et al, 2003) and thus may reduce the potential risk of soil erosion (Barthès and Roose, 2002;Leguédois and Le Bissonais, 2004;Cantón et al, 2009). …”
Section: Introductionmentioning
confidence: 99%